Analysis of antinuclear antibody titers and patterns by using HEp‐2 and primate liver tissue substrate indirect immunofluorescence assay in patients with systemic autoimmune rheumatic diseases. Issue 12 (13th October 2020) - Wei, Qiujing; Jiang, Yutong; Xie, Jiewen; Lv, Qing; Xie, Ya; Tu, Liudan; Xiao, Min; Wu, Zhongming; Gu, Jieruo
Abstract: Background: Indirect immunofluorescence assay (IIFA) is viewed as a preliminary standard to assess antinuclear antibodies (ANAs). Our aim was to explore ANA positivity rate, titers, and patterns in patients with systemic autoimmune rheumatic diseases (SARD), including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), primary Sjögren's syndrome (pSS), systemic sclerosis (SSc), and mixed connective tissue disease (MCTD), compared with healthy controls (HC). Methods: Assess antinuclear antibody titers and patterns were retrospectively identified and compared by IIFA using human epithelial cells (HEp‐2) and primate liver tissue substrate according to international consensus in SARD. Serum complement 3 (C3), C4, and immunoglobulin G were compared among subgroups with different ANA titers. The positive predictive values (PPV) for different ANA titers were calculated. Results: There were a total of 3510 samples, including 2034 SLE, 973 RA, 155 SSc, 309 pSS, and 39 MCTD cases. There was no difference in age between HC and SARD, excluding RA. ANA positivity rate in SARD and HC was 78.7% and 12.2%, respectively. A titer of ≥1:320 revealed a PPV of 84.0% in SARD. SLE patients with ANA titers ≥1:320 had significantly lower levels of C3 and C4. AC‐4 (31.2%) was the major pattern in patients with SARD, followed by AC‐5 (23.9%) and AC‐1 (18.8%). SLE mostly presented with AC‐4 (30.3%). Several mixed patterns provided a significant hint for SSc and SLE. The major pattern in HC was AC‐2 (12.2%). Conclusions: Assess antinuclear antibody positivity, titers, and patterns display differences in various SARD, contributing to the classification of SARD. Abstract : Testing of antinuclear antibodies (ANAs) by indirect immunofluorescence assay (IIFA) provides valuable information on ANA titers and patterns especially in patients with systemic autoimmune rheumatic diseases (SARD). We analyzed a total of 3510 SARD cases and found that ANA positivity rate in SARD and healthy individuals was 78.7% and 12.2%, respectively. A titer of ≥1:320 revealed a positive predictive value of 84.0% in SARD. Systemic lupus erythematosus (SLE) patients with ANA titers ≥1:320 had significantly lower levels of complement 3 and complement 4. The AC‐4 pattern (31.2%) was the major pattern in patients with SARD, followed by AC‐5 (23.9%) and AC‐1 (18.8%). SLE mostly presented with AC‐4 (30.3%). Several mixed patterns provided a significant hint for systemic sclerosis (SSc) and SLE.